Philosophy of Science (Epistemology of Science) - Nanat Fatah Natsir; Erni Hayanti; Habibah Nur Azizah; Ikhsanul fauzi; Kiki MIftahul Hakiki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In the modern era, advances in technology and information impact all aspects of human life, both personally and socially, including the human mind. The ease of accessing information through sophisticated technology, the rapid flow of information, and the ease of access even across continents, have led to a sense of dependency and weakened reasoning, making it easy to believe in inaccurate information or knowledge. To avoid these negative impacts, one needs to understand the origins, methods, steps, and procedures that enable the acquisition of knowledge. The purpose of this article is to understand how something becomes true knowledge, and how it aligns with human reason and logic. This study utilizes library research, utilizing library materials as the primary source. The approach employed a qualitative approach. The results show that epistemology is a specialized field of philosophy that aims to acquire knowledge about knowledge. In this case, it is knowledge derived from conscious sensory absorption, whether old or newly acquired. Scientific knowledge can be considered true when we draw correct conclusions. This inference process is called logic.